Automated NMR resonance assignments and structure determination using a minimal set of 4D spectra - Thomas Evangelidis (Nature Portfolio, 2018)
Further automation of NMR structure determination is needed to increase the throughput and accessibility of this method. Here the authors present 4D-CHAINS/autoNOE-Rosetta, a complete pipeline that allows rapid and fully automated structure determination from two highly complementary NMR datasets.